Dynamic Energy Modeling of Battery Climate System in an Electric Vehicle - Jog, Priyanka; Venkatesh, Varun (My University, 2017)
With ever increasing environmental awareness , electric vehicles have gained focus in the current market scenario and are developing fast. Electric vehicles are emission free, have lower energy consumption and maintenance cost. However, there has been constant strive to enhance the range and performance of the electric vehicles as that of conventional combustion vehicles. The primary challenge associated with an electric vehicle is frequent charging and discharging cycles which causes heat generation within the battery cells. This in turn reduces the performance and lifetime of the battery if not monitored. Thus it is necessary to have a thermal management system to control the thermal behaviour of the battery. However, battery thermal management system also consumes energy from battery affecting the range of the vehicle. Thus it is also necessary to monitor the energy consumption of the thermal management system. The main aim of this thesis is to model a generic thermal management system for the battery and other auxiliary components of an electric vehicle using a lumped system approach using the tool SIMULINK. The lumped system approach will be benchmarked with the 1D CFD approach by comparing with the model developed using the commercial tool GT-SUITE. Also, the thermal management system model developed in SIMULINK will be integrated with the ÅF’s complete vehicle energy model to monitor the energy consumption and range of the vehicle. The model shall be flexible to simulate different types of cooling and heating systems. The model shall be able to accommodate different drive cycles and ambient climatic conditions. The energy model for thermal management system of battery, propulsion system and passenger compartment has been developed. The model is capable of predicting the thermal behaviour of the system as well as the energy consumption and range of operation. It is flexible for different driving cycles and ambient conditions, which is developed using lumped system analysis. Comparisons with 1D CFD approach was found in good agreement.
Keywords: Energi; Transport; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Strömningsmekanik och akustik; Energy; Transport; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Fluid Mechanics and Acoustics